3D Organisation of Cells in Pseudostratified Epithelia - Iber, Dagmar; Vetter, Roman (Frontiers in Physics, 2022)
When the position of the cell nuclei in an epithelial tissue is distributed in a way suggestive of a stratified epithelium even though it is comprised of a single cell layer, the epithelium is said to be pseudostratified. Pseudostratified epithelia often have smooth apical and basal surfaces, yet along the apical-basal axis, their cells assume highly dynamic, irregular shapes. Here, we review a recently developed new perspective on epithelial cell organisation, introducing the term “punakoid” to describe the complicated cell shape found in pseudostratified epithelia. Punakoids directly interact with many more cells inside the tissue than what is visible at either of its surfaces. Seemingly random at first sight, the cell packing configurations along the entire apical-basal axis actually follow a set of fundamental geometrical relationships. These were recently shown to arise from the minimisation of lateral cell-cell contact energy for a given variability in the cross-sectional cell areas. The complex three-dimensional cell neighbour relationships in pseudostratified epithelia thus emerge from a simple physical principle. This paves the way for the development of data-driven 3D computer simulations that will be invaluable to advance our understanding of epithelial dynamics in development and disease.